2019
DOI: 10.1159/000503600
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Electrical Stimulation of the Otolith Organ: Preliminary Results in Humans with Bilateral Vestibulopathy and Sensorineural Hearing Loss

Abstract: Introduction: Bilateral vestibulopathy is an important cause of imbalance that is misdiagnosed. The clinical management of patients with bilateral vestibular loss remains difficult as there is no clear evidence for an effective treatment. In this paper, we try to analyze the effect of chronic electrical stimulation and adaptation to electrical stimulation of the vestibular system in humans when stimulating the otolith organ with a constant pulse train to mitigate imbalance due to bilateral vestibular dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…Electrical stimulation induces myogenic responses in the vestibulocollic pathway as has already been established before (15). We observe that otolith organ electrical stimulation can restore the vestibulocollic reflex in patients with BVD and vestibular implant, in all cases in this study, with an important effect on the clinical situation and BVD symptoms restoration (17). The shape of the EcVEMP was similar to the conventional acoustically elicited cVEMP.…”
Section: Vestibularsupporting
confidence: 77%
See 3 more Smart Citations
“…Electrical stimulation induces myogenic responses in the vestibulocollic pathway as has already been established before (15). We observe that otolith organ electrical stimulation can restore the vestibulocollic reflex in patients with BVD and vestibular implant, in all cases in this study, with an important effect on the clinical situation and BVD symptoms restoration (17). The shape of the EcVEMP was similar to the conventional acoustically elicited cVEMP.…”
Section: Vestibularsupporting
confidence: 77%
“…In all cases, acoustic VEMP responses were present before cochlear implant implantation. In the vestibular implant group, three patients had bilateral vestibular dysfunction (BVD) and met the inclusion criteria for vestibular implantation research, which have been described in detail in a previous study ( 17 ). All three of these patients also had severe hearing loss.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, vestibular implants ( 29 ) may also constitute a treatment option for patients with bilateral vestibulopathy after meningitis. Ramos Macias et al recently demonstrated that otolith organ implantation was feasible in two patients with bilateral vestibulopathy due to meningitis ( 30 ). Plausibly, this procedure may have a window of opportunity as for cochlear implantation, due to progressing ossification of the inner ear fluid compartments ( 21 ).…”
Section: Discussionmentioning
confidence: 99%